On-Line PAT Monitoring of Lucentis in the Fermenter Using Aptamer-Based Capacitive Microfluidic Chip Biosensor. Issue 5 (1st May 2022) - Bhardwaj, Tanu; Jha, Sandeep Kumar
Abstract : In this study, we have developed an aptamer-based PDMS/glass microfluidic chip biosensor employing the capacitance based method of detection, which has the tendency to work as an on-line Process Analytical Technology (PAT) monitoring tool to detect Lucentis in the fermenters. The limit of detection (LOD) and linear range of detection of the chip was determined to be 8.5 nM and 8.5−100 nM, respectively which was better than HPLC based method of Lucentis estimation. In real sample analysis, a significant correlation was obtained between the reported microchip based biosensor and HPLC-based detection method. Moreover, pre-concentration or pre-processing of media broth was not necessary with our method, which reduced the analysis time to 30 min. The chip was determined to be miniaturized, selective, specific, interference-free, label-free, rapid, and reusable with a long shelf-life. Additionally, the chip demonstrated the requirement of a small direct sample volume of 10 μ l and simple automation using a peristaltic pump. The chip biosensor is expected to have on-line PAT monitoring use for checking the production of Lucentis in the fermenter leading to a reduction in the cost of the therapy and better affordability of the treatment to the age-related macular degeneration (AMD) patients.